Especulação fundiária e vazios urbanos em Marechal Cândido Rondon/PR: o interesse privado intervindo às determinações da função social da cidade e da propriedade urbana - Hoffmann, Matieli Cardoso Alves (2020)
This research discusses the production of the urban space of Marechal Cândido Rondon considering its relations between land speculation, urban voids and land income, that is, the private interests of landowners that overlap slithers on what determines the social function of the city and urban property. From a literature review that covers the knowledge of urban policy, land speculation and land income sought to understand the aspects inherent to land concentration, one questions the way in which urban voids have organized the space for land use and occupation. This process makes access to land selective, on the other hand, determining urban expansion in a scathing and speculative way, favoring the obtaining of differential income in central urban voids. Within this perspective it is understood that the formation of these voids and their capitalist strategies in the interest of land income appropriation, have been obstacles to the fulfillment of the social function of urban property. Urban property when it does not comply with the social function, prevents the population from having access to urbanized land, that is, the right to the city, the main guideline of the social function of the city. This process becomes even more complex when analyzing how the municipal government governs urban policy on land ownership, the income of land is approved, however, it is denied that the impoverished population has the right to the city.